TINJAUAN KELENGKAPAN PENGISIAN FORMULIR RINGKASAN PASIEN PULANG RAWAT INAP DI RUMAH SAKIT YPK MANDIRI 2022 - Elvira Xandra Ximenes Harum; Laela Indawati (Bajang Institute, 2023)
Filling in the completeness of the patient's medical resume at the YPK Mandiri Hospital is still not optimal where there are still many summary of discharged patients that have not been filled out completely. In accordance with service standards, the minimum quality of medical records, the completeness of filling out a summary of discharge patients must be 100%. The purpose of this study was to see the completeness of filling out the inpatient summary form. This study uses quantitative analysis methods. Most of the inpatient discharge summaries have been completed in accordance with the SOP, only at the stage of filling out the discharged patient summaries by doctors it has not been carried out properly. Based on the results of the recapitulation of the completeness of filling out the summary form for inpatient discharge in a quantitative analysis of 75 medical records, the results obtained are 85% complete. The highest percentage is found in the Completion of Important Reports/Forms and Author Authentication components, which is 86%, while the lowest presentation is in the Patient Identification component, which is 84%. The percentage of completeness of the 4 components above is 85%. Constraints in the filling process related to the completeness of filling out the Discharge Patient Summary in the medical records of inpatients, namely due to the doctor's lack of thoroughness in filling out the summary of inpatient discharge patients and also the lack of socialization carried out by the hospital about how important the items in the summary of inpatient discharge patients should be filled out. as a whole in order to get an effective medical record.